Manajemen Pemasaran PKBM (Pusat Kegiatan Belajar Masyarakat) - Karlis Karlis; Dety Mulyanti (Universitas 45 Surabaya, 2023)
Growth in the number of people is increasing every year. This causes many children to drop out of school, so relevant institutions are needed to support this. It is not an easy thing to persuade people to want to send their children who have dropped out of school because there is no money or work. Apart from the age required to continue formal schooling, embarrassment is also the biggest obstacle, not to mention the fact that there are too many lessons left behind. Therefore, a certain strategy or technique is needed to attract the public's interest in enrolling or sending children who drop out of school to PKBM. Among the various strategies that can be used by managers is to involve various elements as a reference in carrying out marketing strategies, namely product, price, place, promotion, people, psychological evidence, process. This research is in the form of library research by collecting data from books, journals and dictionaries, archives related to the problem. This research is descriptive qualitative.